Pengaruh Store Atmosphere, Display Product, Dan Hedonic Shopping Motivation Terhadap Impulse Buying Pada Konsumen Alfamart Di Kabupaten Boyolali - Farihin, Nadhif Rahman; Kuswati, Rini (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The development of the retail industry in Indonesia has experienced significant growth in recent decades. The presence of various modern retail chains such as Alfamart, Indomaret, and other minimarkets has changed people's consumption patterns.